Effect of work life balance on turnover intention among academic staffs in UiTM Melaka Kampus Bandaraya / Norida Aya and Nur Syuhada Azamai @ Azami - Aya, Norida; Azamai @ Azami, Nur Syuhada (Faculty of Business and Management, 2015)
Work life balance is very important in the work place especially among academic staffs in Malaysia public higher education institutions. Work life imbalance will be effect job satisfaction and organizational commitment, reduce work effort, reduced performance, and increased absenteeism and turnover. The aim for this study was to examine the relationship between work life balance of academic staffs in UiTM Melaka Kampus Bandaraya and their turnover intention. The study used questionnaires of academic staffs from UiTM Melaka Kampus Bandaraya. A total of 66 usable responses were received from the questionnaires survey. The responses from the sample are used to test the hypotheses that family leave, flexible work arrangement and child care centre have relationship with turnover intention. The results indicated that there was significant relationship between family leave and turnover intention among academic staffs. Meanwhile, there was no significant relationship between flexible work arrangement and child care centre towards on turnover intention. The findings of this study will help in terms of understanding the state of work life balance of academic staffs and its relationship with turnover intention. It was hoped that the findings of this study would add a large sample from other public or private universities in Malaysia and focus among public and private universities academic staffs.